2009
DOI: 10.1111/j.1468-2982.2008.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Trigeminal Neuralgia Following Cerebellar AVM Embolization With Onyx

Abstract: Intracranial arteriovenous malformation (AVM) is a rare cause of trigeminal neuralgia (TN). Successful resolution of AVM-related TN following embolization surgery using Onyx has not been reported. In this case report, a posterior fossa AVM was embolized in two separate, staged endovascular surgeries using Onyx. The AVM was reduced in size, and the TN resolved. The patient subsequently underwent radiosurgery for the small, residual AVM, and he has maintained an uneventful follow-up. A thorough literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…In AVM‐associated TN, similar symptoms are thought to arise from the nerve's contact with abnormal vascular structures of the AVM [3] (as in the earlier case), micro‐AVMs intrinsic to the nerve or brainstem [8], or arterialized veins in the nerve's vicinity [5]. Recent reports of embolization of posterior fossa AVMs [18,19,21,26] and dAVFs [6] have shown promise in treating AVM‐associated TN, suggesting an endovascular analog to microvascular decompression.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In AVM‐associated TN, similar symptoms are thought to arise from the nerve's contact with abnormal vascular structures of the AVM [3] (as in the earlier case), micro‐AVMs intrinsic to the nerve or brainstem [8], or arterialized veins in the nerve's vicinity [5]. Recent reports of embolization of posterior fossa AVMs [18,19,21,26] and dAVFs [6] have shown promise in treating AVM‐associated TN, suggesting an endovascular analog to microvascular decompression.…”
Section: Discussionmentioning
confidence: 88%
“…Treatment of AVM‐associated TN has included standalone or combination therapy consisting of percutaneous procedures (thermocoagulation, balloon compression, or glycerol injection) [1,2,8–12], surgical microvascular decompression, or AVM extirpation [3,5,7,8,13,14], and stereotactic radiosurgery [15–17]. Recently, endovascular embolization of aberrant vasculature has emerged as a treatment strategy for AVM‐associated TN [6,18–21]. We report a case of a child with TN from a large posterior fossa AVM in whom repeated embolization of vascular feeders in contact with the V2 division provided only temporary relief.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that treatment of nidus reduced blood flow and the size of the feeder, which resolved pulsatile compression of the trigeminal nerve and remitted TGN. 4, [9][10][11][12][13] Since the present case had high-grade AVM, nidus treatment was included in multimodal treatment aiming at elimination of the hemorrhagic risk and treatment of TGN. It was planned to perform excision after multistage embolization and add MVD as the (PCA), and anterior choroidal artery, and the drainers were the great cerebral vein of Galen, basal vein of Rosenthal, and vein of Labbe, and the condition was Spetzler-Martin (SM) grading scale Grade IV (Figs.…”
Section: Case Presentationmentioning
confidence: 99%
“…When symptoms are not improved by multimodal treatment, application of MVD should be investigated. Other than direct surgery, it has been occasionally reported that (7) SRS alone was effective, 8) (8) embolization alone was effective, [10][11][12][13] and (9) SRS was performed after embolization. 9) When the risks of excision and MVD are expected to be high, noninvasive modalities, such as SRS and embolization, may be investigated.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation